Expert Consensus Methods In The Humanities: An Exploration of their Potential [version 2; peer review: 2 approved, 1 approved with reservations] - Lex Bouter; Tamarinde Haven; Lidwine B. Mokkink; Rik Peels; Charlotte C.S. Rulkens (F1000Research)
Background Despite the significant role of consensus and dissensus in knowledge production, formal approaches to consensus are notably less common in the humanities compared to their frequent application in natural, social, and life sciences. This article therefore explores the potential of expert consensus methods in humanities-related research. Methods In order to do so, an interdisciplinary team of both sciences researchers experienced in consensus methods and researchers familiar with the domain of the humanities and epistemology, conducted a literary review and exchanged their expertise in multiple brainstorm sessions. Results This resulted in the identification of six key elements of expert consensus methods. It also provided for an overview of different types of expert consensus methods that regularly used in the natural, social, and life sciences: Delphi studies, nominal groups, consensus conferences, and Glaser’s state of the art method and illustrative examples from both sciences and humanities-related studies. An overview of possible purposes for applying these methods is provided to identify the research contexts in which these methods have proven their value, which can be extrapolated to humanities related issues for which these methods seem promising. Conclusions The comparisons and categorisation show that, when focusing on the purposes, there seem to be humanities-related issues that may lend themselves better to structured expert consensus methods than their subject matter and research methods might suggest. When deliberately applied in context chosen by researchers with expertise in a specific humanities domain, expert consensus methods can accelerate epistemic process, enhance transparency, increase replicability, stimulate diversity, and encourage fair processes in humanities research and the application of its findings.